Adapting to Climate Change Implications of Risk-Based Approaches - Morsut, Claudia; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2026)
Climate change adaptation has become the new mantra worldwide as the set of strategies, practices, and measures for coping with climate change and building resilient societies. Accompanying its rise on the international agenda, especially since the Paris Agreement, is the treatment of climate change adaptation using a risk management approach. This Open Access book examines risk management as a type of policy logic that shapes and refracts the outcomes of climate change adaptation. Policy logics are underpinned by a set of ontological understandings of the nature of problems and how they should be handled, along with certain methodologies for analysing and acting upon those problems. Policy logics, in other words, are not politically neutral. Risk management approaches offer systematised models for making assessments and a clear set of decision tools. They also, however, may underestimate complexity, exclude wider social goals and trigger new unknown risks. This book offers a novel view on climate change adaptation by critically questioning the use of a risk management approach. Empirically, the book expands our understanding of which climate change adaptation policies are being adopted, at international and national levels. Theoretically, the book considers two sets of literatures enlightening the implications of a risk approach to the governance of extreme events: Security Studies and Risk Governance. Each of these fields is mined for key insights into the advantages and drawbacks of risk management. Analytically, the book assesses international and national policies in the light of these advantages and drawbacks and discusses the resulting implications at practical level. Claudia Morsut is an associate professor of societal security in the Department of Safety, Economics and Planning at the University of Stavanger, Norway. She holds a PhD in international relations from the University la Sapienza, Rome, Italy. She studies the European Union$1 (Bs security governance, risk management and civil protection, climate change, and climate change adaptation in a multi-governance setting.s
Chapter 01: The Relevance of Risk-based Approaches in Climate Change Adaptation -- Chapter 02: Understanding Risk from different Disciplines -- Chapter 03: Systemic Risk Governance for Disaster Risk Management and Climate Change Adaptation -- Chapter 04: International climate change adaptation governance: The evolution of risk management models -- Chapter 05: Legitimation of Climate Change Adaptation Policies in Norway: Intersections between Societal Planning, Technological-administrative and Societal Security Discourses -- Chapter 06: On flood Risk and the Relationship between Climate Change Adaptation, Prevention, and Preparedness -- Chapter 07: Implications of a risk management approach within climate change adaptation for research and practice.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Security, International; Political science; Environmental policy; Environmental law, International; International Security Studies; Politics and International Studies; Environmental Policy; International Environmental Law